Tsetse peritrophic matrix influences for trypanosome transmission. (October 2019) - Aksoy, Serap
Graphical abstract: Highlights: Tsetse PM is constitutively produced by cardia and lines the entire gut. PM prevents epithelial immune induction against resident microbiota. PM is a physical barrier trypanosomes must bypass for transmission. Trypanosomes modify tsetse microRNA-275 in cardia to reduce PM synthesis. Obligate symbiont Wigglesworthia influence PM development in larva. Abstract: Tsetse flies are important vectors of parasitic African trypanosomes, agents of human and animal trypanosomiasis. Easily administrable and effective tools for disease control in the mammalian host are still lacking but reduction of the tsetse vector populations can reduce disease. An alternative approach is to reduce the transmission of trypanosomes in the tsetse vector. The gut peritrophic matrix (PM) has emerged as an important regulator of parasite transmission success in tsetse. Tsetse has a Type II PM that is constitutively produced by cells in the cardia organ. Tsetse PM lines the entire gut and functions as an immunological barrier to prevent the gut epithelia from responding to commensal environmental microbes present in the gut lumen. Tsetse PM also functions as a physical barrier to trypanosome infections that enter into the gut lumen in an infective blood meal. For persistence in the gut, African trypanosomes have developed an adaptive manipulative process to transiently reduce PM efficacy. The process is mediated by mammalian trypanosome surface coat proteins, Variant Surface Glycoproteins (VSGs) which are shed in the gut lumen and taken up by cardia cells. The mechanism of PM reduction involves a tsetse microRNA (miR-275) which acts thru the Wnt signaling pathway. The PM efficacy is once again reduced later in the infection process to enable the gut established parasites to reenter into the gut lumen to colonize the salivary glands, an essential process for transmission. The ability to modulate PM integrity can lead to innovative approaches to reduce disease transmission.